Use of subordinated sentences in the written narrative discourse by elementary students - Araya, Claudia; Aravena, Sergio; Cifuentes, Dayanne; Gaete, Sofía; López, Vanessa; Sepúlveda, Consuelo (Árboles y Rizomas, 2021)
The objective of this study is to describe the syntactic complexity present in the written narrative corpus of 3rd, 5th and 7th grade students in two types of educational establishments. It seeks to determine in detail the characteristics of the sentences used in the corpus in terms of their complexity (number, use of simple and subordinate sentences, and types of subordinate sentences used) in each of the school levels studied. In addition, it seeks to establish whether there are differences related to the type of educational establishment in which these samples were taken. Regarding this last point, there were no differences of any kind. On the other hand, the results show a sustained development in terms of the number of subordinate sentences that are produced from one school level to the next and a decrease in the use of simple sentences. Regarding the types of subordinate sentences present in the corpus, there is a greater use of substantive subordinate sentences (carried out, for the most part, through infinitive verbs) and of adverbial subordinate sentences of time, mode and cause over the other types of sentences. Finally, it is concluded that the processes of complexity of narrative discourse could be supported through a focus not only centered on teaching particular strategies for the production of this type of discourse in superstructural terms, but also accompanied by models of syntactic production of growing complexity.
Keywords: syntactic development; subordinate sentences; writing; schooling